Women’s empowerment in agriculture and agricultural productivity: Evidence from rural maize farmer households in western Kenya - Dirro, Gracious M.; Seymour, Greg; Kassie, Menale; Muricho, Geoffrey; Muriithi, Beatrice Wambui (Public Library of Science, 2018)
This paper documents a positive relationship between maize productivity in western Kenya and women’s empowerment in agriculture, measured using indicators derived from the abbreviated version of the Women’s Empowerment in Agriculture Index. Applying a cross-sectional instrumental-variable regression method to a data set of 707 maize farm households from western Kenya, we find that women’s empowerment in agriculture significantly increases maize productivity. Although all indicators of women’s empowerment significantly increase productivity, there is no significant association between the women’s workload (amount of time spent working) and maize productivity. Furthermore, the results show heterogenous effects with respect to women’s empowerment on maize productivity for farm plots managed jointly by a male and female and plots managed individually by only a male or female. More specifically, the results suggest that female- and male-managed plots experience significant improvements in productivity when the women who tend them are empowered. These findings provide evidence that women’s empowerment contributes not only to reducing the gender gap in agricultural productivity, but also to improving, specifically, productivity from farms managed by women. Thus, rural development interventions in Kenya that aim to increase agricultural productivity—and, by extension, improve food security and reduce poverty—could achieve greater impact by integrating women’s empowerment into existing and future projects.